The Role Of Consumer Satisfaction In Mediating Factors Affecting Omnichannel-Based Repurchase Intention - Abdullah, Lukman Zaini; Junianingrum, Sherli (LPPM ISNJ Bengkalis, 2024)
This study analyzed the effect of product diversity, service quality, and perceived value on repurchase intention mediated by omnichannel-based consumer satisfaction. The population of this study were Indonesian citizens aged over 17 years who impulsively buy their daily needs online and offline, the number of which is unknown. The sampling technique used random sampling, with sample measurement using the Hair approach, to obtain a sample of 250 respondents. Primary data were collected through questionnaires distributed online and analyzed using SEM-PLS with the help of the SmartPLS application. The results showed that product diversity, service quality, and satisfaction positively affected repurchase intention, while perceived value did not affect repurchase intention. Furthermore, product diversity and service quality positively affected satisfaction, while perceived value did not affect satisfaction. Satisfaction can mediate the effect of product diversity and service quality on repurchase intention, while satisfaction cannot mediate the effect of perceived value on repurchase intention. Theoretically, this study can add insight and be a reference for further research on repurchase intention. In practice, this research provides recommendations and an overview of omnichannel marketing-based business units in meeting consumer needs.